2011
DOI: 10.1016/j.tube.2011.10.018
|View full text |Cite
|
Sign up to set email alerts
|

The ΔfbpA attenuated candidate vaccine from Mycobacterium tuberculosis, H37Rv primes for a stronger T-bet dependent Th1 immunity in mice

Abstract: Summary The ΔfbpA candidate vaccine derived from Mycobacterium tuberculosis (H37Rv) protects mice better than BCG against tuberculosis, and we investigated the hypothesis that ΔfbpA may induce a stronger Th1 immunity. Since T-bet transcription factor regulates Th1 immunity, mice infected with ΔfbpA, BCG vaccine and related mycobacteria were analyzed for T-bet positive T cells. Mouse dendritic cells (DCs) or macrophages were also pulsed with excretory-secreted antigens (ES; Antigen-85B, ESAT-6 and CFP10) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Given the major role, it plays in eliciting protective adaptive immunity , autophagy induction is being examined as a novel strategy to enhance the efficacy of TB vaccines currently under development. In mice immunized with DCs infected with vaccine candidate Δ fbpA attenuated Mtb and treated with rapamycin, T‐helper cell‐mediated protection was induced in response to virulent Mtb . The same study showed that enhanced immunogenicity of BCG overexpressing Ag85B is associated with increased macrophage autophagy.…”
Section: Autophagy Contribution To Mycobacterial Killing and Antigen mentioning
confidence: 85%
“…Given the major role, it plays in eliciting protective adaptive immunity , autophagy induction is being examined as a novel strategy to enhance the efficacy of TB vaccines currently under development. In mice immunized with DCs infected with vaccine candidate Δ fbpA attenuated Mtb and treated with rapamycin, T‐helper cell‐mediated protection was induced in response to virulent Mtb . The same study showed that enhanced immunogenicity of BCG overexpressing Ag85B is associated with increased macrophage autophagy.…”
Section: Autophagy Contribution To Mycobacterial Killing and Antigen mentioning
confidence: 85%
“…T cells from spleens were also stained for multifunctional cytokines after they were re-stimulated with a soluble protein antigen from Mtb Erdman as described before. 124 Purified protein antigens used for recall immune responses (ESAT-6, CFP-10, antigen-85B were from BEI (NIH). IFN-γ assays were performed by stimulating splenocytes using specific protein antigens added at 1 µg/mL and 18 h supernatants assayed for IFN-γ using sandwich ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to BCG vaccine manipulations, using the Mtb platform to derive vaccines deleting secretory products appears encouraging. The ∆secA-∆lysA and ∆fbpA-sapM and mutants were more effective than BCG [116,152,183] and are potential booster vaccines for BCG-vaccinated infants. Among these, the ∆secA-lysA strain has an excellent safety profile in mice [183] compared to ∆fbpA-sapM, qualifying it for clinical trials.…”
Section: Status Of Mycobacterial Vaccines Deficient In Secreted Prote...mentioning
confidence: 96%
“…To our knowledge, this is the first study demonstrating that an Mtb mutant lacking a secretory protein antigen is effective as a vaccine against TB. The ∆fbpA candidate vaccine induced high levels of phagosome maturation, proinflammatory cytokines, and Th1 immune response and an increased expansion of CD4+ CXCR3+ IFN-γ+ cells in mice after vaccination [116]. Although recombinant mycobacterial strains over-expressing Ag85B (FbpB) and Ag85C (FbpC) also protect mice against TB [106,117], thus far, Mtb mutants 'lacking' these proteins have not been tested for vaccine efficacy.…”
Section: Ag85 Complexmentioning
confidence: 99%